A Springtime Journey to the Soviet Union: Postwar Planning and Policy Mobilities through the Iron Curtain. (11th March 2014) - Cook, Ian R.; Ward, Stephen V.; Ward, Kevin
Abstract This article builds upon a relatively small but growing literature in geography, planning and cognate disciplines that seeks to understand the variegated geographies and histories of policy mobilities. The article uses a case study of an exchange trip between town planners in the Soviet Union and the UK between 1957 and 1958. It focuses on the experiences of the British planners in the Soviet Union and sets the tour within the wider context of a fluctuating and sometimes turbulent history of Anglo‐Soviet politics, travels and connections. In doing this, the article makes three arguments: first, there is much to be gained by bringing together the geography‐dominated policy mobilities literature with that on exchanges and visits by architects, engineers and planners. Secondly, the greater sensitivity to the histories of policy mobilities allows contemporary studies to be contextualized in the longer history of organized learning between different urban professions. Thirdly, despite the long history of policy mobilities, what differentiates the current era from previous eras is the prominent 'knowledge intermediary' roles now played by consultancies and think tanks. As the article will demonstrate, it was branches of government and professional bodies, rather than consultancies and think tanks, that tended to dominate such roles previously.